Bioengineering and in utero transplantation of fetal skin in the sheep model: A crucial step towards clinical application in human fetal spina bifida repair. (29th November 2019) - Mazzone, Luca; Moehrlen, Ueli; Ochsenbein‐Kölble, Nicole; Pontiggia, Luca; Biedermann, Thomas; Reichmann, Ernst; Meuli, Martin
Abstract: An intricate problem during open human fetal surgery for spina bifida regards back skin closure, particularly in those cases where the skin defect is much too large for primary closure. We hypothesize that tissue engineering of fetal skin might provide an adequate autologous skin substitute for in utero application in such situations. Eight sheep fetuses of four time‐mated ewes underwent fetoscopic skin biopsy at 65 days of gestation. Fibroblasts and keratinocytes isolated from the biopsy were used to create fetal dermo‐epidermal skin substitutes. These were transplanted on the fetuses by open fetal surgery at 90 days of gestation on skin defects (excisional wounds) created during the same procedure. Pregnancy was allowed to continue until euthanasia at 120 days of gestation. The graft area was analyzed macroscopically and microscopically. The transplanted fetal dermo‐epidermal skin substitutes was well discernable in situ in three of the four fetuses available for analysis. Histology confirmed healed grafts with a close to natural histological skin architecture four weeks after in utero transplantation. This experimental study generates evidence that laboratory grown autologous fetal skin analogues can successfully be transplanted in utero. These results have clinical implications as an analogous procedure might be applied in human fetuses undergoing prenatal repair to facilitate primary skin closure. Finally, this study may also fertilize the field of fetal tissue engineering in general, particularly when more interventional, minimally invasive, and open fetal surgical procedures become available.